A cross-sectional survey about behavior of wearing condoms among college students who engage in sexual activity: the mediating role of attitudes of preventive behavior - Qi, Li; Guo, Ronghuang; Qu, Yi; Li, Xiaomei (Frontiers in Public Health, 2025)
Background and objectivesAlthough the global human immunodeficiency virus (HIV) infection rate has decreased in recent years, the proportion and number of HIV-infected individuals aged 18–24 years has increased. The main mode of HIV transmission is sexual, a large proportion of the infected population are college students, and numerous health education activities have been implemented to prevent HIV infection, where mastery of relevant knowledge greatly improves. Nevertheless, the effectiveness of necessary protective measures is not ideal during actual behavior, indicating insufficient conversion of prevention knowledge to behavioral. To understand the factors and interactions that influence preventive behavior, we conducted a cross-sectional exploratory study.Materials and methodsParticipants (n = 1,111) were students from Heilongjiang Province. A survey questionnaire was distributed through online social platforms. The questionnaire collected data on sociodemographic variables, perception of infection risk (PIR), perceived benefits of preventive behavior (PBPB), perceived disorders of preventive behavior (PDPB), attitudes of preventive behavior (APB), and behavior of wearing condoms (BWC).ResultsBWC did not differ significantly according to gender, academic qualification pursued, or subject major (p ≥ 0.05), but did differ significantly based on sexual orientation, receiving HIV infection prevention education, and commercial and casual sexual behaviors. No significant correlation was detected between PIR and APB (p ≥ 0.05), while PBPB and APB were significantly positively and PDPB and APB significantly negatively correlated (p < 0.05). Further, there was no significant correlation between PBPB and BWC (p ≥ 0.05), while PIR and APB were positively correlated with BWC (p < 0.05), and there was a negative correlation between PDPB and BWC (p < 0.05). APB did not mediate between PDPB and BWC, but APB partially mediated between PDPB and BWC, accounting for approximately 9.96% of the total effect value, and played a fully mediating role (100%) between PBPB and BWC.ConclusionOur analysis indicates that PBPB acts on BWC through APB, PIR directly affects BWC, and PDPB can directly affect BWC, while also influencing BWC through APB. Future efforts to increase PBPB, PIR, and APB, reduce PDPB, and promote the use of condoms in sexual behavior among college students are warranted.